Potensi Dana Alternatif Pengembangan Ekonomi Lokal Melalui Pameran Pembangunan Kabupaten Bekasi Tahun 2018 - Pandji Sukmana; Ismi Nuryati Rochayah (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
This study focuses on the potential and alternatives of local economic development through the 2018 Bekasi Regency Development Exhibition. The local economic potential is owned by Bekasi Regency in each sub-district. And through the Development Exhibition in Bekasi Regency, namely the Bekasi Regency Fair in 2018, products from the local economy of each district are promoted. The method used in this research is qualitative method. The theory used is the theory of the implementation of Edward III's public policy that uses communication variables, namely transmission, clarity and consistency. Based on research conducted in the Bekasi Regency Fair in 2018 successfully developed the local economy by promoting its products on the stands available at the exhibition area. This success is due to the implementation of public policies that they do meet the variables of communication, namely transmission, clarity and consistency.